2008
DOI: 10.1104/pp.108.119636
|View full text |Cite
|
Sign up to set email alerts
|

Novel Properties of the Wheat Aluminum Tolerance Organic Acid Transporter (TaALMT1) Revealed by Electrophysiological Characterization in Xenopus Oocytes: Functional and Structural Implications

Abstract: Many plant species avoid the phytotoxic effects of aluminum (Al) by exuding dicarboxylic and tricarboxylic acids that chelate and immobilize Al 31 at the root surface, thus preventing it from entering root cells. Several novel genes that encode membrane transporters from the ALMT and MATE families recently were cloned and implicated in mediating the organic acid transport underlying this Al tolerance response. Given our limited understanding of the functional properties of ALMTs, in this study a detailed chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
124
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(126 citation statements)
references
References 30 publications
2
124
0
Order By: Relevance
“…Furthermore SLAC1 shares neither structural nor functional similarities to AtALMT1, the Arabidopsis orthologue to the wheat aluminum-induced malate channel (48). Thus SLAC1 represents a novel type of inorganic anion channel with unknown tertiary structure, but kinetic properties very similar to the slow anion channel first described with Xanthium strumarium and Vicia faba guard cells (49,50).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore SLAC1 shares neither structural nor functional similarities to AtALMT1, the Arabidopsis orthologue to the wheat aluminum-induced malate channel (48). Thus SLAC1 represents a novel type of inorganic anion channel with unknown tertiary structure, but kinetic properties very similar to the slow anion channel first described with Xanthium strumarium and Vicia faba guard cells (49,50).…”
Section: Discussionmentioning
confidence: 94%
“…3B). The putative elevated relative malate permeability in planta likely results from malate transporters expressed in addition to SLAC1 in guard cells such as AtALMT-type carriers or AtABCB14 (48,51,52).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed analysis of the wheat ALMT1 revealed that the channel is activated with a Km1/2 of 5µM and is strongly rectifying (Pineros et al 2008). However, the exact binding site and mechanism of Al 3+ channel activation awaits elucidation.…”
Section: On the Role Of Malate As A Component Of The Root Exudatesmentioning
confidence: 99%
“…Limited information is available for comparison of anion selectivity in oocytes expressing plant transporters. It has been shown that GmN70, an anion transporter on the symbiosome membrane, favors NO 3 2 transport (Vincill et al, 2005), and TaALMT1 favors malate transport but can be selective for Cl 2 under certain conditions (Pineros et al, 2008 ) and has the same charge and oxyanion characteristics, which seem to be required for selective transport by HvPHT1;6. NO 3 2 is also an oxyanion, but is smaller in size, and has only a single negative charge, whereas Cl 2 is much smaller and does not have the oxygen.…”
mentioning
confidence: 99%